Analisis Bibliometrik: Peran Humas Perguruan Tinggi - Daud, Yusri M (Intelektualita: Journal of Education Sciences and Teacher Training, 2025)
This study aims to analyze the role of public relations in higher education through a bibliometric analysis approach. The research gap identified in this study is the limited comprehensive study that specifically links the results of bibliometric analysis with the strategic role of public relations in building an image, reputation, and institutional communication in the higher education environment. This study uses a bibliometric analysis method based on Google Scholar indexed article data collected through the Publish or Perish (PoP) software in the period 2020–2025, with a maximum of 1000 relevant articles. Data processing is done using Microsoft Excel and visual mapping is done through the VOSviewer application. Analysis was carried out on publication trends, keyword distribution, and thematic linkages through overlay and density visualization. The results of the study show that the main themes that dominate the literature on the role of public relations in higher education are "public relations", "higher education", and "public relations". There are several main clusters on the keyword map, but topics such as public relations digitization, social media, communication innovation, and relationships with external and internal stakeholders have not emerged dominantly, so there are still research opportunities in this area. The overlay visualization marks the emergence of new issues in the 2022–2023 period, while the density visualization shows three main density centers with the core theme of public relations and higher education, and the low-density area as new research opportunities. Therefore, this study emphasizes that the role of public relations in universities is in a strategic position to build the image, reputation, and competitiveness of institutions in the digital era and increasingly dynamic global competition. The research recommends the need to develop research on the relationship between the role of public relations and digitalization, innovation, social responsibility, and broader relationships with stakeholders to support adaptive and professional public relations management in the modern higher education environment